The Prevention of Ischemia-Reperfusion Injury in Elderly Rats after Lower Limb Tourniquet Use - Borja Herrero de la Parte; Javier Roa-Esparza; Iñigo Cearra; Inmaculada Ruiz Montesinos; Daniel Alonso-Alconada; Ana Alonso-Varona; Carmen Mar Medina; Sira Iturrizaga Correcher; Ignacio García-Alonso (MDPI AG, 2022)
Background: Lower limb ischemia-reperfusion injury (IRI-LL) is a common major complication of orthopedic surgery, especially in elderly patients. It has previously been demonstrated that folinic acid (FA) reduced IRI-LL damage in 3-4-month-old rats. This current work analyses the effect of FA in the prevention of IRI-LL in elderly animals. Methods: Forty-two 18-month-old male WAG/RijHsd rats were subjected to 3 h of ischemia. Eighteen animals received FA (2.5 mg/kg, ip) 20 min before the end of the ischemia period, while the other half received the same volume of saline solution. The animals were sacrificed after 3 h, 24 h, and 14 days of reperfusion for biochemical (tissue damage markers and electrolytes), histopathological studies of the gastrocnemius muscle and the daily assessment of the limb function by the Rota Rod test, respectively. Results: The administration of FA prior to the end of the ischemia period reduced the increase in LDH and CK observed in non-treated animals by 30-40% (p < 0.0001). When the histological sections were analyzed, FA was found to have reduced the number of damaged muscle fibers per field by 20% (60 ± 17.1 vs. 80.7 ± 16.4, p < 0.0001). The functional test revealed that FA also led to an improvement in the muscle function, assessed by the length of time that the animals kept running on the rod, compared to untreated animals. Conclusions: The administration of FA, prior to the end of the ischemic period, decreases the damage induced by IRI-LL, also achieving a faster recovery of mobility.